Hypersensitivity Reaction to a Mosquito Bite in a Patient with Chronic Myeloid Leukemia. (5th October 2011) - Dior, Uri P.; Salameh, Shaden; Gershinsky, Yonatan; Stalnikowicz, Ruth
Abstract : A twenty-one-year-old male patient with an exaggerated hypersensitivity reaction to a mosquito bite presented to the department of emergency medicine for further evaluation. He was noted on physical examination to have splenomegaly. The hematological blood tests that were performed were compatible with chronic myeloid leukemia (CML). In this case, the mosquito bite heralded the diagnosis of CML.